An epidemic of tomato leaf curl disease in Jammu - H.S. CHIB; C.S. KALHA, KRISHNA KUMAR, RAJEEV MAHAJAN (Indian Phytopathology, 2004)
Field surveys were conducted in the autumn of 1999-2000 and 2000-2001 in the rain-fed tomato growing belt of Akhnoor of Jammu and leaf curl incidence ranging between 80.00 to 98.00 per cent was recorded in different villages. The symptoms of the disease included curling of leaf lamina and stunting of infected plants, even yellowing in severe cases. The disease was successfully transmitted through graft and whitefly transmission but not by sap inoculation. Electron microscopy revealed the presence of geminate particles in leaf dip preparations. Lantana spp., Hibiscus spp., Ageratum spp., Carica spp., Malvastrum spp. and Euphorbia spp. in and around tomato growing fields of Akhnoor were observed as alternate perennial hosts of whitefly in off-season. These alternate hosts probably act as year-round virus and/or whitefly reservoirs. On the basis of mode of transmission, symptomatology, host range studies, the virus was identified as whitefly transmitted geminivirus naturally occurring in tomato hitherto not reported from Jammu and Kashmir. Among six dates of transplanting from 10th August to 25th of October, maximum yield (65.20 q ha-1) was observed in 1st September transplanted crops, which has lowest monetary loss of Rs. 1.04 lakh ha-l.